Experimental study on the peeling characteristics of wax on the surface of plastic alloy pipe and glass steel pipe. Issue 2 (May 2020) - Liu, Wei; Ding, Haopeng; Wu, Yan; Miao, Kun; Deng, Zhian; Wen, Ziyan
Abstract: Plastic alloy pipes and glass steel pipes are two widely used non-metallic pipes. In this paper, sliced paraffin was used to perform waxing and peeling experiments on the lining surfaces of two types of pipes, investigating the effects of temperature and wax thickness on the surface peeling force of two types of pipe line. This experimental study has certain guiding effect on the selection of non-metallic pipes and the design of the wax removal device.